EVALUASI PELAKSANAAN PROGRAM PERBAIKAN INFRASTRUKTUR JALAN DI KECAMATAN MARPOYAN DAMAI TAHUN 2012 - Pohan, Rima Melati; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Pekanbaru City Government through Bappeda (Planning Board) Pekanbaru City has made a program called RKPJM (Work Plan medium term) of Pekanbaru. Where in the city of Pekanbaru Regional Regulation No. 19 Year 2012 on Regional Medium Term Development Plan 2012-2017 Pekanbaru City Year. It is intended that the Development that has direncana run in accordance with what has been planned by the City of Pekanbaru.The purpose of this research is to determine the extent to which the conduct of the program development or improvement of the road where the Department of Public Works as on education (regional work units) PDid has been run in accordance with what has been planned and laid Musrenbang RKPD location within the city of Pekanbaru. This study was conducted in 2012 Year of Peace Marpoyan Where the informants in this study are those who understand the problems that occur Pekanbaru City Public Works Department officials, the District officers and officials of Peace Marpoyan Bappeda Pekanbaru. In pengumpalan the data obtained from the documentation and in-depth interviews to the informant. Having collected and then analyzed using descriptive analysis.Evaluation of the implementation of the program can be known from its implementation. Does the implementing of these programs succeed or fail. In implementing a program must menenukan constraints faced by the implementing agency of the program activities.Keywords : policies, programs, improvement of road infrastructure